THE CONTRIBUTION OF HEALTH LAWS IN ADDRESSING NATIONAL HEALTH ISSUES: A LITERATURE REVIEW - Gunawan Widjaja; Hotmaria Hertawaty Sijabat; Handojo Dhanudibroto (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The Health Law No. 17 of 2023 contributes substantially to strengthening Indonesia's national health system. Through regulatory simplification, governance strengthening, and emphasis on promotive and preventive efforts, this law encourages the creation of more equitable, high-quality, and responsive health services to contemporary challenges, including disasters and epidemics. This transformation is also supported by improved legal protection for health workers, strengthening the domestic health industry, and integrating the national health information system. However, the effectiveness of the implementation of this law still faces various challenges, such as disparities in access in remote areas, limitations in human resources and infrastructure, and the need for adjustments at the professional and community levels. Synergy between the central and regional governments, health workers, and active community involvement are key to ensuring that this policy runs optimally and has a real impact on improving the health of the community. Overall, Health Law No. 17 of 2023 is a step forward in the reform of the national health system. With commitment, oversight, and strong collaboration from all stakeholders, it is hoped that this law will be able to realise an inclusive, resilient, and sustainable health system for the welfare of all Indonesians.